2008
DOI: 10.1109/jstsp.2008.924384
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Sparse Signals Using Sparse Measurement Matrices in Compressed DNA Microarrays

Abstract: Abstract-Microarrays (DNA, protein, etc.) are massively parallel affinity-based biosensors capable of detecting and quantifying a large number of different genomic particles simultaneously. Among them, DNA microarrays comprising tens of thousands of probe spots are currently being employed to test multitude of targets in a single experiment. In conventional microarrays, each spot contains a large number of copies of a single probe designed to capture a single target, and, hence, collects only a single data poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
131
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(131 citation statements)
references
References 35 publications
0
131
0
Order By: Relevance
“…Such block-sparse signals arise in various application problems, say, DNA microarrays [7,8], equalization of sparse communication channels [9], source localization [10], wideband spectrum sensing [11], and color imaging [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such block-sparse signals arise in various application problems, say, DNA microarrays [7,8], equalization of sparse communication channels [9], source localization [10], wideband spectrum sensing [11], and color imaging [12].…”
Section: Introductionmentioning
confidence: 99%
“…The compressed sensing (CS) involves recovery of the unknown sparse signal from this linear system [1]: y = Φx, where x is an unknown signal of length N, Φ ∈ R M×N (M<N) is the measurement matrix, y denotes the observation vector of length M . This problem has been widely applied in sparse channel estimation [2] and remote spectral sensing [3]. Since M<N, it is ill-posed to reconstruct x given y.…”
Section: Introductionmentioning
confidence: 99%
“…If in addition to sparsity, the signal representation is also structured in the form of clustered non-zeros, the signal would be referred to as being block-sparse. In practice, block-sparsity can be found in multi-band signals [2] or in the measurements of gene expression levels [3]. It has been shown that exploring the block-sparsity enables robust signal recovery from fewer compressive measurements [4].…”
Section: Introductionmentioning
confidence: 99%